Analisis Karakteristik Bahan Alam Sebagai Adsorben Pada Pengkondisian Udara Adsorpsi - Bramastha, Aqsal Raja; Sucipta, Made; Wijaksana, Hendra (Teknik Desain Mekanika; Vol 11 No 1 (2022): Januari 2022 : Teknik Desain Mekanika, 2022)
Abstract To feel comfortable and cool in a room, an air conditioning (AC) system is used which is uses a compressor and requires a large amount of electrical energy, thereby increasing global warming and the occurrence of an energy crisis. Referring to this, a cooling system that is more environmentally friendly, efficient, save energy is needed. One of the alternative is use natural materials as adsorbents in adsorption air conditioning. In this system, changes in moisture content occur due to the process of absorption of air moisture in each test material in the packed bed. This study aims to determine the regeneration characteristics of natural materials, activated carbon, as well as their performance against moisture. The characteristics tested also include contact angle test and proximate test. In addition to the type of material, mass variations of 200gr, 400gr, and 600gr are also carried out as well as variations in the combination between materials. The results obtained from the regeneration test 9 times, natural ingredients have an effect on air conditioning. The larger the mass tested, the greater its ability to reduce humidity. In another sense, 600gr activated carbon provides the most optimal performance among other natural materials, mass variations and combined variations. Keywords: Adsorption air conditioning, natural materials, characteristics, regeneration, and humidity